Metal pattern-based planar sub-THz filter in coplanar waveguide on optically transparent substrate - Jaroslav Havlíček; Daniel Havelka; Michal Cifra (Scientific Reports, 2025)
Abstract The sub-terahertz and terahertz frequency bands (0.1–10 THz) hold immense potential for revolutionizing diverse fields, ranging from advanced telecommunications to biomedical diagnostics and structural biology. Despite the rapidly growing interest in these frequencies, there is a significant gap in the development of compact, high-performance sub-terahertz devices on optically transparent substrates. Such substrates are crucial for integration with optical microscopy and spectroscopy techniques, enabling applications in biophysics and material sciences. To address this technology gap, this paper presents the design, fabrication, and measurement of a compact band-stop filter unit operating in the sub-terahertz F-band (90–140 GHz) on an optically transparent substrate. The unit utilizes a $$λ$$ /4 open-end folded stub resonator structure integrated within a coplanar waveguide. Different coupling variants between the stub and coplanar waveguide were analyzed using frequency domain simulations. The device is compatible with advanced optical microscopy techniques since it is implemented on an optically transparent quartz glass substrate. This feature enables future applications in spectroscopy or biophysics thanks to straightforward integrability with microfluidics. The unit can be cascaded into a higher-order filter to enhance its performance.